2024
DOI: 10.3389/fcell.2024.1332506
|View full text |Cite
|
Sign up to set email alerts
|

Biological clock regulation by the PER gene family: a new perspective on tumor development

Kai Chen,
Yaohui Wang,
Dengxiong Li
et al.

Abstract: The Period (PER) gene family is one of the core components of the circadian clock, with substantial correlations between the PER genes and cancers identified in extensive researches. Abnormal mutations in PER genes can influence cell function, metabolic activity, immunity, and therapy responses, thereby promoting the initiation and development of cancers. This ultimately results in unequal cancers progression and prognosis in patients. This leads to variable cancer progression and prognosis among patients. In-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…Circadian CGs, particularly the PER gene family, play a crucial role in cancer progression and patient prognosis[ 194 ]. Mutations in these genes can affect cell function, metabolism, immunity, and response to treatment, contributing to varying cancer outcomes[ 194 , 195 ].…”
Section: Prognostic Value For Circadian Clock Genes In Cancer Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Circadian CGs, particularly the PER gene family, play a crucial role in cancer progression and patient prognosis[ 194 ]. Mutations in these genes can affect cell function, metabolism, immunity, and response to treatment, contributing to varying cancer outcomes[ 194 , 195 ].…”
Section: Prognostic Value For Circadian Clock Genes In Cancer Diagnosismentioning
confidence: 99%
“…Circadian CGs, particularly the PER gene family, play a crucial role in cancer progression and patient prognosis[ 194 ]. Mutations in these genes can affect cell function, metabolism, immunity, and response to treatment, contributing to varying cancer outcomes[ 194 , 195 ]. Studies have shown that the expression levels of circadian genes are significantly altered in cancers such as colorectal carcinoma, HER2-positive advanced gastric cancer, BC, pancreatic cancer, and obesity-related cancers[ 196 - 200 ].…”
Section: Prognostic Value For Circadian Clock Genes In Cancer Diagnosismentioning
confidence: 99%
See 1 more Smart Citation